2003
DOI: 10.1080/00015458.2003.11679445
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Rupture of the Thoracic Aorta

Abstract: Traumatic rupture of the thoracic aorta is a life threatening situation, and may be secondary to several mechanisms; mainly penetrating or iatrogenic lesions and blunt trauma. Although penetrating mechanisms predominate, the number of patients with aortic disruption due to blunt trauma has continued to increase. This paper shows an overview focusing on the pathogenesis, diagnosis, timing and type of treatment regarding traumatic injuries of the thoracic aorta; it also reports the experience of one single cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Because of the serious comorbidities seen in these patients, aortic repair often has to be postponed because the invasive character of the open surgery results in unacceptably high risks for these patients. 33,34 Some studies have shown that mortality of the open aortic repair can be decreased when deliberately delayed surgical repair is performed. 10,[35][36][37] Still, even with careful blood pressure monitoring, approximately 2% to 5% of the patients experience a total aortic rupture, mostly within 1 week after the trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the serious comorbidities seen in these patients, aortic repair often has to be postponed because the invasive character of the open surgery results in unacceptably high risks for these patients. 33,34 Some studies have shown that mortality of the open aortic repair can be decreased when deliberately delayed surgical repair is performed. 10,[35][36][37] Still, even with careful blood pressure monitoring, approximately 2% to 5% of the patients experience a total aortic rupture, mostly within 1 week after the trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to BTAR, this study demonstrates that complex secondary flows in the aorta may still develop without chest trauma in car accidents. Whether the corresponding transverse wall shear stress could actually cause rupture may not be the case, however it may have a significant role in explaining why rupture sometimes occurs away from the aortic isthmus such as in the ascending or descending aorta (Chiesa et al, 2003) or in the absence of any thoracic injury whatsoever (Sevitt, 1977). With regard to the most damaging scenario, it is difficult to draw from this study due to the interplay between wall shear stress magnitude and duration.…”
Section: Discussionmentioning
confidence: 92%
“…Blunt traumatic aortic rupture (BTAR) is the seconding leading cause of death in car accidents in North America, responsible for 7500 to 8000 casualties per year (Richens et al, 2002). Victims of BTAR have a rather grim fate with an estimated 70 to 90% of patients dying on site, and of those fortunate survivors an additional 40 to 50% are estimated to succumb to their injuries within 24 h (Chiesa et al, 2003). Although vehicle safety systems have undoubtedly advanced over the past decade, their effectiveness in preventing BTAR is minor, as the incidence of Email addresses for correspondence: † g dilabb encs.concordia.ca; ‡ lcfd encs.concordia.ca arXiv:1812.06844v1 [physics.flu-dyn] 17 Dec 2018 BTAR has remained unchanged regardless of airbag system and seat belt use (Sznol et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of aortic lacerations have focused on the location of lacerations along the axis of the aorta and the presence of other impact wounds in the body (27), clinical diagnosis and treatment (811), or physical mechanisms of wounding (1213), but have provided little detail on the morphology of aortic lacerations and the overlying mediastinal serosa.…”
Section: Introductionmentioning
confidence: 99%